Intellectual Property Indicators in the Mesoregions of the State of Alagoas-Brazil - Pereira de Morais, Luanna; Nunes de Queiroz, Silvana; Quintino Furtado , Cristiano; Francisco da Silva, Gabriel (International Journal for Innovation Education and Research, 2020)
The objective of this study is to analyze local, innovative and sustainable development in the three Mesoregions of Alagoas, through intellectual property indicators (patents, trademarks, industrial design and geographical indications). The methodology consists of the analysis of secondary sources extracted from the Statistical Database on Industrial Property (BADEPI), available on the website of the National Institute of Industrial Property (INPI), for the years 2010 to 2017. The results point out marked differences, with the eastern Alagoas mesoregion concentrating the intellectual property indicators with two geographical indications, 95.93% of the patent deposits and 84.73% of the deposits of trademark registrations, as well as industrial designs and computer programs. Agreste Alagoano presents a reasonable amount of intellectual protection, with emphasis on the municipality of Arapiraca. Sertão Alagoano, on the other hand, has the worst situation, low amount of intellectual property, even in a region with a diversified cultural and environmental environment. Thus, it was found that the Mesoregions of Alagoas need an ecosystem that invests in the innovation process in the region, especially the Sertão Alagoano.